MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DALAM MENENTUKAN KALIMAT UTAMA MENGGUNAKAN MODEL PBL, NHT DAN SNOWBALL THROWING - Elisa, Herni Noor; Mahmuddin, Mahmuddin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The limitation of students' critical thinking skills in Indonesian learning is a problem in this study. Students fail to solve problems, make decisions, and understand the text being read. Implementing Problem Based Learning (PBL), Number Head Together (NHT) Combination, and Snowball Throwing is an attempt to address this problem. The purpose of this study is to improve the critical thinking skills of students in grade 4 of SDN Berangas Timur 1, which consists of 25 students. This research was conducted in 3 meetings. Data were analyzed using descriptive techniques. The results of observation of teacher activities, student activities, critical thinking skills, and student learning outcomes are presented in the form of tables and graphs. Each indicator shows the success of teacher activities, student activities, critical thinking skills, and the achievement of individual and classical student learning completeness. The results showed that teachers' activities improved, with a score of 31 for the